Changes overtime in the proportion of beans in a varietal mixture - Dessert, J.M. (1987)
Ten bean var. with different seed color and size, ranging from 21 to 42 g/100 seeds, were planted in Rubona, Rwerere, and Karama (Rwanda) to monitor the change in proportion of var. within the mixtures over the course of seasons and compare these changes with pure stand yields. Over 5 seasons the proportion of var. changed considerably at all 3 sites. Av. pure stand yield and change in proportion of var. over seasons at Rwerere are included. In general, var. with higher pure stand yield or with small seed size increased in proportion at all 3 sites of the study. (CIAT)